Breeding records of Leptotila rufaxilla (Aves: Columbidae) in southwestern Brazilian Amazon with notes on nesting in some regions of occurrence - Lima, Jônatas (2021)
We present new aspects of breeding biology of Gray-fronted Dove Leptotila rufaxilla, from five nests found between 2012 and 2014 in a lowland forest fragment in southwestern Brazil. The nests simple/platform shape were built at a mean height of 1.90 m above ground. The clutch size was two eggs white and elliptic, incubated for 15 days (based on three nests). We recorded predation in two nests still in incubation phase. Minimum hatch weight of nestlings was 10 g and young fledged with a mean mass of 56 g. The constant growth rate (K) of nestlings was 0.40 with a growth asymptote of 60.7 g. Daily survival rate, Mayfield and apparent nesting success in the incubation period was 90, 20 and 56%, respectively, while in the nestling period were all 100%. Our data and the contribution of citizen science showed that L. rufaxilla breeds over the year, mainly in the rainy season, both in southwestern Amazonia and in other regions of occurrence.